Challenges to the Sustainability of Urban Cultural Heritage in the Anthropocene: The Case of Suzhou, Yangtze River Delta, China - Yong Huang; Michael Edward Meadows (Land)
Among the diverse challenges to the sustainability of China’s rich tangible cultural heritage, climate change, associated with increased temperatures, altered precipitation regimes, and the augmented frequency and magnitude of extreme events, is regarded as one of the most prominent. However, there is a diverse range of rapidly emerging environmental and socio-economic hazards that threaten cultural heritage in the country but have thus far received scant attention in this context. Without adequate attention and intervention, the sustainability of the country’s historic urban heritage is highly vulnerable. Anthropocene threats to this important legacy include climate change, sea level rise, land subsidence, water and air pollution, rampant urbanization, and tourism. Suzhou, situated in the low-elevation Yangtze River delta within one or two meters of current sea level, lies in the heart of one of the fastest socio-economically developing and urbanizing regions in the world and is especially vulnerable to the range of threats. As one of the jewels in the crown of China’s architectural heritage, Suzhou represents a model case in which to consider the conflicting interests of socio-economic development and environmental and cultural conservation in the context of rapidly changing environmental conditions. In this review, we consider the diverse risks to the sustainability of Suzhou’s cultural heritage posed by these circumstances, highlight key problems, and prioritize the most urgent issues requiring attention. In recognizing the spatial and temporal nature of these multiple challenges, we highlight the need for integrated approaches to safeguard the sustainability of such valuable resources. Moreover, considering the imperative of accelerating progress towards the UN Sustainable Development Goals and reflecting on current theories of sustainable management of urban cultural heritage, we outline the potential policy and practice implications for the conservation of Suzhou’s historic buildings, canals, and gardens.